A case report of necrotizing soft tissue infection of the chest wall: Effective management with serial debridement. (May 2021) - Fujii, Masakazu; Imamura, Kiyotaka; Kato, Kentaro; Takada, Minoru; Ambo, Yoshiyasu; Nakamura, Fumitaka; Hirano, Satoshi
Abstract: Introduction: Necrotizing soft tissue infection (NSTI) of the chest wall is a rare, rapidly spreading, highly lethal surgical disease. Radical debridement interferes with the important anatomical function of the chest wall. We report a case of chest wall NSTI that was successfully managed with early diagnosis and serial debridement. Presentation of case: A 43-year-old, previously healthy woman presented with severe malaise and worsening right axillary pain. She was severely lethargic and had a painful, large, pale lesion with surrounding erythema of the right chest and trunk. Computed tomography revealed NSTI, with diffuse soft tissue inflammation extending from the axilla to the lower abdomen. There was no obvious entry portal. Prompt surgical drainage was established. Group A streptococcus infection was diagnosed. During her 3-month postoperative course, she underwent four more surgeries, including two debridements. This treatment proved successful and avoided the need for complicated muscle flap reconstruction. She was discharged on postoperative day 109. Discussion: Group A streptococcus can cause NSTI even in immunocompetent patients without an entry portal. Radical debridement is recommended for infection control. Preserving anatomical chest wall function, however, is also important. Serial debridement with close follow-up solved the problem in this patient. Conclusions: Serial debridement with close follow-up enabled to avoid large tissue deficits and complicated reconstruction in the case of NSTI of the chest wall. Highlights: Necrotizing soft tissue infection of the chest wall is rare and lethal. Radical debridement could interfere with the anatomical function of the chest wall. Adequate drainage with minimum skin incision avoids large tissue defects. Serial debridement with close follow-up enabled to avoid complicated reconstruction